Universal Cloud Controller (UCC), a Cloud-centred system using personal mobile devices to control public devices - Thanh Tam, Tran (2016)
We engage different working environments on a daily basis, including private and public environments. When we move from one to another constantly, the data also need to be transferred, and while the private environment is convenient, working with public devices creates the irritation of authentication. This dissertation proposes Universal Cloud Controller (UCC), a multi-components system that improves user’s experience when exchange data from personal to public device. The main functions of the system are to provide a selection mechanism to eliminate the authentication, and an instantly, smoothly, and conveniently data transferring and manipulation solution between user’s personal devices and public devices. We described UCC in both user’s perspective and technical specification, addressing the challenges of designing and developing the system and also proposing the solution. Technologies and related studies were also investigated to learn from their advantages and limitations. Consequently, a working prototype was constructed based on the design and used for a study to evaluate the usability of UCC. The results proved that the designed system is potential and promising for public release, but also contained flaws and limitations. Finally, the paper concluded the topic and suggested future works.